2017
DOI: 10.1590/abd1806-4841.20175150
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor overexpression in miniaturized follicles in female pattern hair loss

Abstract: The etiopathogenesis of female pattern hair loss is still poorly understood. In addition to genetic and hormonal elements, environmental factors could be involved. The aryl hydrocarbon receptor is expressed in keratinocytes and can be activated by environmental pollutants leading to alterations in the cell cycle, inflammation, and apoptosis. Here we demonstrate the overexpression of nuclear aryl hydrocarbon receptors in miniaturized hair follicles in female pattern hair loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Oxidative stress, perifollicular microinflammation, and microvascular insufficiency have been reported as factors associated with AGA. 72 , 73 Goldman et al observed that in AGA, bald areas have lower oxygen (O 2 ) levels than non-bald ones, suggesting some degree of microvascular insufficiency. 74 Moreover, the conversion of testosterone into DHT preferentially occurs in an O 2 -poor medium, and therefore, an increased blood supply would reduce local hypoxia and thus could be beneficial in the treatment of AGA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress, perifollicular microinflammation, and microvascular insufficiency have been reported as factors associated with AGA. 72 , 73 Goldman et al observed that in AGA, bald areas have lower oxygen (O 2 ) levels than non-bald ones, suggesting some degree of microvascular insufficiency. 74 Moreover, the conversion of testosterone into DHT preferentially occurs in an O 2 -poor medium, and therefore, an increased blood supply would reduce local hypoxia and thus could be beneficial in the treatment of AGA.…”
Section: Methodsmentioning
confidence: 99%
“… 1 In addition to the role of androgens, most clearly demonstrated in male AGA, there is evidence of the participation of genetic, hormonal, and environmental elements. 1 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…One study investigating the pathophysiology of androgenetic alopecia found overexpression of nuclear aryl hydrocarbon receptors in the keratinocytes of miniaturized follicles. The authors hypothesized that aryl hydrocarbon receptor stimulation promotes apoptosis via the Fas and TNF-related apoptosis-inducing ligand (TRAIL) pathways, thus promoting follicular regression and miniaturization [48]. Other studies have implicated these receptors in HF regeneration and cycling [49].…”
Section: Polyaromatic Hydrocarbonsmentioning
confidence: 99%
“…The effects of pollutants on skin barrier and ECM homeostasis have been widely reported but effects on hair follicles and scalp skin have been poorly characterized. Ramos PM has reported that AhR overexpression in the nucleus was observed in miniaturized hair follicles in female pattern hair loss [12].…”
Section: Introductionmentioning
confidence: 99%